Axial compressive behaviour of steel-jacket retrofitted RC columns with recycled aggregate concrete. (15th June 2017) - He, An; Cai, Jian; Chen, Qing-Jun; Liu, Xinpei; Xue, Hua; Yu, Chenjie
Highlights: Axial compression tests on steel-jacket retrofitted columns with RAC were undertaken. Variable Poisson's ratio of material was considered in the finite element model. Developed an axial load capacity design model for the retrofitted columns. Abstract: It is an effective solution to strengthen structural column by using steel jacket and infill concrete for reinforced concrete (RC) structure retrofitting. In this research, the recycled aggregate concrete (RAC) is adopted as an infill concrete instead of using the normal concrete, in order to reduce the carbon footprint of construction. Fifteen columns including twelve steel-jacket strengthened columns, one unstrengthened column and two concrete filled steel tube (CFST) columns are tested to investigate the axial compressive behaviour of steel-jacket retrofitted RC columns with RAC. The variables among the tested specimens include the recycled coarse aggregate replacement ratio, RAC strength, steel tube thickness and preload of original column. Experimental results illustrate that using steel jacketing approach for retrofitting could significantly improve the strength, stiffness and ductility of the columns. The axial compressive strength of the steel-jacket retrofitted column with RAC is slightly lower than the one with normal infill concrete, but the influence of recycled coarse aggregate replacement ratios is negligible. The peak strengths of steel-jacket retrofitted columns can be significantly enhanced by increasing the thickness of steel tube. The performances of the steel-jacket retrofitted columns are similar to that of the CFST columns. The effect of the preload of original column on the ultimate strength of steel-jacket retrofitted column is limited. A finite element (FE) model is also developed by using ABAQUS software to simulate the performance of steel-jacket retrofitted columns. The accuracy of the model is validated through comparing with the experimental results. By using the developed FE model, the mechanical behaviour of the column is further discussed in details and extended parametric studies are undertaken to elucidate the effects of various influencing factors on the behaviour of the column and its components. The design methods for predicting the axial compressive strength of the retrofitted column with RAC are suggested.